Changes in the Essential Oil Composition in the Needles of Scots Pine (Pinus sylvestris L.) Under Anthropogenic Stress - Asta Judzentiene; Aida Stikliene; Eugenija Kupcinskiene (The Scientific World Journal)
Unfavorable anthropogenic factors, such as air pollution, lead to biochemical responses in trees. Changes in the amounts of secondary metabolites may be early indicators of invisible injuries. The aim of this study was to evaluate composition of the essential oils in the needles of Scots pine (Pinus sylvestris L.) growing in the areas affected by pollutant emissions of main factories in Lithuania: a nitrogen fertilizer factory (NFF), a cement factory (CF), and an oil refinery (OR). Totally, 14 pine stands were examined along transects from the factories (July 2005). Volatile components of the needles were extracted and analyzed by GC and GC/MS. Over 70 components of the essential oils were identified in current-year and 1-year-old needles.